2022
DOI: 10.3389/fpsyg.2022.1082578
|View full text |Cite
|
Sign up to set email alerts
|

The role of spiritual mindset and gender in small business entrepreneurial success

Abstract: IntroductionSpirituality can be understood as a capital based on individual capabilities created by the application of intrinsic spiritual values, in order to use and develop human potential. The literature points out that spiritual capital increasingly influences and motivates entrepreneurs.MethodsIn this paper, we investigate whether spirituality has a mediating role between psychological resilience, optimism and entrepreneurial success, and verify the gender differences. Our hypotheses are quantitatively te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 84 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…The social and communal settings of religion and spirituality remain profoundly important in meaning pursuit. And spirituality was presented as a positive mediator between psychological resilience and success ( Margaça et al, 2022 ). A study shows that beliefs and life goals can help to develop wellbeing ( Cotton et al, 2009 ).…”
Section: Theoretical Grounding and Hypothesesmentioning
confidence: 99%
“…The social and communal settings of religion and spirituality remain profoundly important in meaning pursuit. And spirituality was presented as a positive mediator between psychological resilience and success ( Margaça et al, 2022 ). A study shows that beliefs and life goals can help to develop wellbeing ( Cotton et al, 2009 ).…”
Section: Theoretical Grounding and Hypothesesmentioning
confidence: 99%
“…Dong highlight the importance of personal traits, such as alertness and risk-taking abilities, in shaping the EI of female engineering students [ 13 ]. Additionally, Margaça underscore the influence of personal background elements, including work experience, marital status, and intrinsic motivation, on EI [ 14 ]. From an external perspective, research by Lin and Dong indicates that university environments and support systems, encompassing aspects like entrepreneurial training and context, critically affect students’ attitudes and perceived behavioral control, thereby impacting their EI [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such adaptability is instrumental in fostering entrepreneurial success 18 . Several studies have demonstrated a strong positive correlation between psychological resilience and entrepreneurial success 19 .…”
Section: Introductionmentioning
confidence: 99%